Diversi Sebagai Bentuk Penyelesaian Perkara Pidana Anak - Dwi Rachma Ningtias; Said Sampara; Hardianto Djanggih (Journal of Lex Generalis (JLG), 2020)
Penelitian ini bertujuan Untuk mengetahui, menjelaskan dan menganalisis pengaturan diversi dalam penyelesaian perkara pidana anak; Untuk mengetahui, menjelaskan dan menganalisis konsep diversi yang ideal dalam penyelesaian perkara pidana anak. Berdasarkan analisis terhadap data dan fakta penulis berkesimpulan bahwa Diversi dalam penyelesaian perkara pidana anak di Indonesia diatur dalam Undang-Undang No. 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak, Peraturan Pemerintah No. 65 Tahun 2015 tentang Pedoman Pelaksanaan Diversi dan Penanganan Anak Yang Belum Berumur 12 (Dua Belas) Tahun, Peraturan Jaksa Agung Republik Indonesia Nomor Per-006/A/J.A/04/2015 tentang Pedoman Pelaksanaan Diversi Pada Tingkat Penuntutan, Peraturan Mahkamah Agung Republik Indonesia No. 4 Tahun 2014 tentang Pedoman Pelaksanaan Diversi dalam Sistem Peradilan Pidana Anak. (2) Konsep diversi yang ideal dalam penyelesaian perkara pidana anak adalah diversi dengan bentuk mediasi penal dan restorative justice. This study aims to analyze diversion arrangements in solving juvenile criminal cases; To find out, explain and analyze the ideal concept of diversion in solving juvenile criminal cases. Based on the analysis of data and facts, the writer concludes that Diversi in solving child criminal cases in Indonesia is regulated in Law no. 11 of 2012 concerning the Juvenile Criminal Justice System, Government Regulation No. 65 of 2015 concerning Guidelines for the Implementation of Diversion and Handling of Children Not Aged 12 (Twelve) Years Old, Regulation of the Attorney General of the Republic of Indonesia Number Per-006 / A / JA / 04/2015 concerning Guidelines for Implementation of Diversion at the Prosecution Level, Regulation of the Supreme Court of the Republic of Indonesia No. 4 of 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Criminal Justice System. (2) The ideal diversion concept in solving juvenile criminal cases is diversion with the form of mediation of penal and restorative justice.